2020
DOI: 10.1021/acschemneuro.9b00633
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of N-Oleoylglycine in a Mouse Model of Mild Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is one of the main causes of death in young people for which currently no efficacious treatment exists. Recently, we have reported that mice with mild-TBI with a specific injury in the insula showed elevated levels of a little investigated N-acyl amino acid, N-oleoylglycine (OlGly). Nacyl amino acids have recently experienced an increased interest because of their important biological activities. They belong to the endocannabinoidome family of lipids with structural similarities wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…The suppression of endogenous OlGly following spontaneous withdrawal from chronic morphine is noteworthy given its previously described neuroprotective properties. In fact, OlGly is elevated in the insular cortex in mice following traumatic brain injury (TBI; Donvito et al, 2019 ) and systemic administration of this compound reduces the behavioral impairments produced by TBI (i.e., motor, anxiety) ( Piscitelli et al, 2020 ) and nicotine withdrawal ( Donvito et al, 2019 ). We ( Petrie et al, 2019 ) have previously reported that ex vivo analysis of tissue from rats experiencing acute naloxone-precipitated MWD revealed that OlGly is elevated in the NAc (but not in the amygdala, PFC and IIC), whereas levels of the endocannabinoids, 2-AG and AEA, and the other endogenous PPARα ligands, OEA, and PEA, were not affected in any of the brain regions evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The suppression of endogenous OlGly following spontaneous withdrawal from chronic morphine is noteworthy given its previously described neuroprotective properties. In fact, OlGly is elevated in the insular cortex in mice following traumatic brain injury (TBI; Donvito et al, 2019 ) and systemic administration of this compound reduces the behavioral impairments produced by TBI (i.e., motor, anxiety) ( Piscitelli et al, 2020 ) and nicotine withdrawal ( Donvito et al, 2019 ). We ( Petrie et al, 2019 ) have previously reported that ex vivo analysis of tissue from rats experiencing acute naloxone-precipitated MWD revealed that OlGly is elevated in the NAc (but not in the amygdala, PFC and IIC), whereas levels of the endocannabinoids, 2-AG and AEA, and the other endogenous PPARα ligands, OEA, and PEA, were not affected in any of the brain regions evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were dounce-homogenized and extracted with chloroform/methanol/Tris-HCl 50 mM pH 7.5 (2:1:1, v/v) containing internal deuterated standards for AEA, 2-AG, PEA, OEA, AraGly, OlGly, and OlAla and N -acylserotonin quantification by isotope dilution (5 pmol for [2H]8AEA; 50 pmol for [2H]52-AG, [2H]4 PEA, [2H]2 OEA; 10 pmol for [2H]4 DHEA and [2H]4 EPEA; 50 pmol for [2H]8AraGly and [2H]2OlGly; 100 pmol for [2H]8OlAla; 50 pmol for [2H]8 AA5HT). Then, the lipid extract was dissolved in 100 ul of CH 3 OH and analyzed by either LC-APCI-MS for AEA, 2-AG, PEA, OEA, DHEA, and EPEA quantification, which were calculated based on their area ratio with the internal deuterated standard signal areas ( Bisogno et al, 1997 ; Piscitelli et al, 2020 ), and by LC-MS-IT-TOF (Shimadzu Corporation, Kyoto, Japan) for N -acylglycine, N -oleoylalanine and N -acylserotonin identification and quantification, using multiple reaction monitoring (MRM). The chromatograms of the high-resolution [M-H]- values were extracted and used for calibration and quantification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the role of the eCBs and eCB-Ls in alcohol use and abuse, we tested the effect of EtOH chronic self-administration on the levels of different eCBs and eCB-Ls, some were shown to have neuroprotective properties [10,17,24,25]. Therefore, female and male mice were tested for EtOH consumption and preference using an intermittent access to EtOH-two bottle choice (IA2BC) procedure, designed to simulate the repeated episodes of heavy drinking and withdrawal that characterize alcohol abuse [26].…”
Section: Intermittent Access To Etoh In a 2-bottle Choice Procedures ...mentioning
confidence: 99%
“…N -oleoyl-glycine (NOleG) has been reported to counteract some of the behavioural consequences of mild trauma in mice [ 120 ]. Importantly, this condition causes elevation of the levels of this compound in the insula [ 121 ]. NOleG also reduces nicotine self-administration as well as some of the signs of withdrawal from chronic or acute morphine administration in rats [ 120 , 122 ].…”
Section: Characteristics and Importance Of Ecbome Mediators From A Nutritional Standpointmentioning
confidence: 99%